Consequences of Varied Planting Geometry and Early Post Emergence Herbicides for Crop-Weed Interventions in Rice Under Semi-Arid Climate - ASHRAF,U. (2016)
ABSTRACT Adjustment of planting geometry along with reduced applications of herbicides can be a viable tool for effective weed management in rice. This present study has examined the effects of three planting geometries (20 cm x 20 cm, 20 cm x 10 cm and 10 cm x 10 cm); along with early post emergence herbicides, viz; bispyribac sodium 20% WP at 39.50 g a.i. ha-1, bispyribac sodium 100 SC at 39.50 g a.i. ha-1, cyhalofop-butyle 10% EC at 49.50 g a.i. ha-1, and penoxulam 240 EC at 15 g a.i. ha-1 on weed growth, and rice performance under semi-arid climate. A weedy check was maintained as control where no herbicide was applied. Results showed that the narrowest plant spacing (10 cm x 10 cm) effectively controlled weeds; however, it also resulted in reduced rice growth and yield. More weed infestation and a season-long weed growth in weedy check plots have damaged rice growth and yield performance. All herbicides were effective in reducing weed density and biomass; however, reductions were greatest for 10 cm x 10 cm spaced plants. Among different plant spacings, the highest grain yield (4.35 ton ha-1) was obtained from plots where rice was planted at 20 cm x 20 cm; while narrowest plant spacing led to reduced tiller production, panicle development, grains per panicle, 1000-grain weight, and grain yield, but increased sterility % and biological yield. Further, weed dry biomass was negatively correlated with grain and biological yield of rice at all spacings. Although narrow plant spacing was effective in controlling weeds, it also reduced rice productivity, suggesting the need for further studies to overcome intra-specific competition in narrow spaced rice plants through improved resource management.